CLINICAL SYMPTOMS AND LABORATORY FINDINGS of COMMON INFECTIONS IN GERIATRIC POPULATION IN TEHRAN (CASE STUDY): Pharmaceutical Science-Medicine - SEPEHR TAGHIZADEH; SHAYAN MONFAREDI ZADEH (International Journal of Life Science and Pharma Research, 2022)
The potential for infection in geriatric population increases to the high rates of infections, the mortality and disability resulting from them and the various signs of infection in the elderly, which can lead to delays in diagnosis. This study was designed to evaluate the clinical symptoms and laboratory findings of infectious diseases in elderly patients hospitalized in infection ward in one of the medical centers of Tehran province. This descriptive study was conducted on 256 elderly patients with an infectious disease in one of the medical centers of Tehran province in 2016. The detection of a fever or a specific infection site in the examination was the criterion for the early diagnosis of the infectious disease. Medical history and physical examination were taken from all of the patients, and laboratory tests including blood culture (CBC, ESR, CRP), urine culture (Color, appearance, specific gravity, Protein, Glucose, Keton Aceton, Blood) diagnostic imaging including sonography, CT scan and MRI, were performed. Then, the questionnaire containing demographic data, clinical symptoms and laboratory findings was completed by interviewing the patients and reviewing their records. The results were presented as descriptive statistics. In this study, out of the 256 patients participating in this study, 135 (53.6%) were male. The average age of patients was 74.3 years old, in which most of them (48.4%) were in the age group of 60-75 years old. The most common complaints were fever (19.4%) and dyspnea (14.9%) and the most common underlying disease was hypertension (37%). The most common infectious diseases were pneumonia (23.4%) and sepsis (15.7%), respectively. The most common infectious diseases leading to hospitalization and death in the elderly are pneumonia and sepsis.